2011
DOI: 10.1103/revmodphys.83.1323
|View full text |Cite
|
Sign up to set email alerts
|

Complexity, segregation, and pattern formation in rotating-drum flows

Abstract: Rotating-drum flows span a variety of research areas, ranging from physics of granular matter through hydrodynamics of suspensions to pure liquid coating flows. Recent years have seen an intensified scientific activity associated with this unique geometrical configuration, which has contributed to our understanding of related subjects such as avalanches in granules and segregation in suspensions. The existing literature related to rotating-drum flows is reviewed, highlighting similarities and differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
103
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(111 citation statements)
references
References 225 publications
(545 reference statements)
7
103
0
1
Order By: Relevance
“…Particles below it (the fixed bed) are in static equilibrium and perform solid body rotation in unison with the container (41)(42)(43). This flow rapidly reaches steady state (10,42), at which point, to a good approximation, the volume fractions and macroscopic (averaged) densities of the material in the flowing layer and the bulk are constant and equal. For a monodisperse granular material, all particles are identical, and c is the concentration of the tagged particles (e.g., black in color), while 1 − c is the concentration of the nontagged particles (e.g., white in color).…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Particles below it (the fixed bed) are in static equilibrium and perform solid body rotation in unison with the container (41)(42)(43). This flow rapidly reaches steady state (10,42), at which point, to a good approximation, the volume fractions and macroscopic (averaged) densities of the material in the flowing layer and the bulk are constant and equal. For a monodisperse granular material, all particles are identical, and c is the concentration of the tagged particles (e.g., black in color), while 1 − c is the concentration of the nontagged particles (e.g., white in color).…”
Section: Modelmentioning
confidence: 99%
“…In particular, granular flow in a long rotating horizontal drum has proven to be a simple but important system to understand (10). Recently, it has been suggested that axial diffusion in this system is anomalous (11).…”
mentioning
confidence: 99%
“…Granular materials and powders in rotating drums are of wide interest not only because of their extensive use in the chemical, minerals, pharmacutical and food processing contexts, but also as model systems in the study of natural disasters, such as avalanches or landslides (Meier et al, 2007;Seiden and Thomas, 2011).…”
Section: Inroductionmentioning
confidence: 99%
“…That is what makes granular science very exciting. If a bidisperse mixture of differently sized grains is rotated horizontally in a cylindrical drum, a complex scenario of segregation processes is found [2]. Radial segregation takes place in the first ≈5 rotations, followed by axial segregation after ≈100 rotations.…”
Section: Introductionmentioning
confidence: 99%